SUPER LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING THE EFFECTIVENESS OF SCHOOL ADMINISTRATION UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON PHANOM - khobchaisaeng, Onuma; Sornphet, Supakorn; Kheawnamchum, Jaruwan (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were to 1)examine and compare the super leadership of school administrators, classified by status and school sizes, 2) examine and compare the effectiveness of school administration, classified by status and school sizes, 3) determine the relationship between the super leadership of administrators and the effectiveness of school administration, and 4) identify the predictive power for the super leadership of administrators affecting the effectiveness of school administration. The sample consisted of 259 participants, including 78 school administrators and 181 teachers. The sample size determination used a 15 percent criterion and was selected through multi-stage random sampling. The research instruments included two sets of 5–rating scale questionnaires: 1) a set of questionnaires about the super leadership of school administrators, with the Index of Item Congruence (IOC) between 0.80 and 1.00, the item discrimination from .53 to 93, and the reliability of .99; and 2) a set of questionnaires about the effectiveness of school administration, with the Index of Item Congruence (IC) between 0.80–1.00, the item discrimination between .34–.94, and the reliability of .98. The statistics employed were percentage, mean, standard deviation, t-test for Independent Samples, One–Way ANOVA, Pearson’s product-correlation coefficient, and Stepwise multiple regression analysis. The research results revealed that: 1. The super leadership of school administrators was overall at the highest level. When classified by status, there were no differences in their leadership level. However, when examining self–leadership on an individual basis, differences were observed at the .05 level of significance. In terms of school sizes, the overall super leadership of school administrators showed no differences. 2. The effectiveness of school administration was overall at the highest level. In terms of status and school sizes, there were no differences. 3. The super leadership of school administrators and the effectiveness of school administration revealed a fairly high level of positive correlation at the .01 level of statistical significance. 4. The four variables of super leadership of school administrators affecting the effectiveness of school administration under the Secondary Educational Service Area Office Nakhon Phanom, namely facilitation (X7), self-leadership (X1), leadership in team building (X6), and rewarding and reprimanding creatively (X5). These aspects could jointly predict at 68 percent. The regression equation of raw scores and standardized scores could be written as follows: Y’ = .91+.30X7+.19X1+.16X6+.14X5 Zy’ =.35 Z7+.24 Z1+.19Z6+.17Z5